LANDSCAPE AND THE GEOGRAPHICAL TURN IN PHOTOGRAPHIC PRACTICE. (4th May 2019) - Dahó, Marta
Abstract : When dealing with the photographic practices that have been of interest over the last two decades in reflecting upon the transformation of territory, a new aim emerges clearly: to unravel the geopolitical dimension of each place. Growing social inequalities and ecological imbalance provoked by globalisation and economic neoliberalism have drawn the attention of many artists. Nevertheless, the interdependence of events in geographically distant places that simultaneously touch upon various spheres of exchange is a particularly difficult subject to grasp in photographic terms. This paper seeks to address this issue by focusing on three recent projects : Nitrate by Xavier Ribas, Copper Geographies by Ignacio Acosta and State Business by Mari Bastashevski. Their works and approaches, closely related to Allan Sekula's seminal practice, contribute to defining how this new geographical premise can manifest in terms of landscape representation, and what challenges are at stake here.